Leveraging Social Media for Da’wah and Waqf: Al-Bahjah’s MIZKA Program in Enhancing Community Engagement and Pesantren Development - Syaefudin, Mochamad; Bakti, Andi Faisal; Islami, Nurul (Kalijaga Journal of Communication, 2025)
Al-Bahjah Islamic Boarding School in Cirebon has intensified promotional efforts to boost community participation in charitable giving, including donations and almsgiving, to support its land endowment (waqf) program and pesantren development through the MIZKA initiative, increasingly utilizing social media as a primary medium. This shift reflects a transition from conventional to digital da’wah models. This study examines the mechanisms of this transition, employing a qualitative approach informed by Anthony Giddens’ structuration theory to analyze interactions between social media and da’wah activities. Findings reveal that pesantren administrators, recognizing technological advancements, leverage social media to sustain da’wah’s core identity. They disseminate Qur’anic verses, hadith, and scholarly opinions to foster followers’ awareness and encourage contributions. The effectiveness of this approach is maintained through transparent social media posts showcasing construction progress and funds raised, establishing a new model of accountability. This indicates that tech-savvy preachers reconstruct social media not only as a tool for outreach but also as a platform for managerial transparency and responsibility.